Pengaruh Teman Sebaya Terhadap Motivasi Belajar Santri Kelas X MA Pesantren Pondok Madinah Makassar - Said, Taufikurrahman; Sampurno, Bambang; Syahrul, Muhammad; Mustamin, Mustamin; Raehana, Syarifa (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study examines the influence of peers on the learning motivation of class X students at MA Pesantren Pondok Madinah, Makassar. The objectives are to describe the characteristics of peers and students' learning motivation, and to analyze the influence between the two. Using a quantitative correlational approach with 30 students as a sample, data were collected through questionnaires and documentation. Data analysis includes validity, reliability, normality, linearity, homogeneity, t-test, and F-test. The results show a moderate relationship between peer interaction and learning motivation. The t-test shows that variables X1 and X4 have a significant effect (p <0.05), while X2 and X3 are not significant. The F-test shows a significant effect of all variables X on Y (p <0.05). In conclusion, the hypothesis is accepted; there is a significant influence of peers on the learning motivation of class X students.